Global Food Commodity Prices and Domestic Food Inflation: Some Insights from Morocco - Mounir EL-KARIMI (New Medit, 2020)
This paper examines the world commodity prices pass-through to food inflation in Morocco, over the period 2004-2018, by using Structural Vector Autoregression (SVAR) model on monthly data. Several interesting results are found from this study. First, the impact of global food prices on domestic food inflation is shown significant, which reflects the large imported component in the domestic food consumption basket. Second, the transmission effect is found to vary across commodities. Consumer prices of cereals and oils significantly and positively respond to external price shocks, while those of dairy and beverages are weakly influenced. Third, there is evidence of asymmetries in the pass-through from world to domestic food prices, where external positive shocks generate a stronger local prices response than negative ones. This situation is indicative of policy and market distortions, namely the subsidies, price controls, and weak competitive market structures. Our findings suggest that food price movements should require much attention in monetary policymaking, especially that the country has taken preliminary steps towards the adoption of floating exchange rate regime.